Workflow interoperability using extensible markup language (XML) - Md Dahalin, Zulkhairi; Wahid, Juliana (IEEE Computer Society, 2002)
States of the art workflow management system (WFMS) do not have adequate features of interoperability among WFMSs that cause incompatible “islands” of process automation within an organization or between organizations. This paper introduces method of interoperability that accommodate the variety of implementation techniques in realizing the WFMS interoperability. To realizing the workflow interoperability, this paper uses two CVFhIS products in the market, i.e. Domino Workflow and Microsoft Exchange 2000 Server. The method that lies in a workflow interoperability framework is a major contribution of this paper. The framework consists of both WFMS products together with two interoperability tools, i.e. Microsoft Exchange Connector for Lotus Notes and Document Object Model (DOM) af Ertensible Markup Language (XML) standard that addressing the communication and exchanging document issues between both WFMS products. To demonstrate the workflow interoperability of our approach, a prototype system has been implemented.